Journalism does not Fit Everybody. Two Points of View: Array - Teodorașcu, Fănel (Acta Universitatis Danubius. Communicatio, 2021)
In this article, we aim at comparing two different visions about journalism. The first one belongs to Mark Twain, himself a former journalist, and was extracted from his novel, A Connecticut Yankee in King Arthur’s Court (1889), while the second one is taken from a newspaper article, published in Adevărul [The Truth], more than eight decades ago. We believe that our research is a salutary / opportune one, and that is why it does not need further justifications.